Central African Republic : Request for Disbursement under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for the Central African Republic. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2020)
While the number of detected cases has so far been limited, the COVID-19 pandemic, if not contained, could have a considerable economic and social impact in C.A.R. and could exacerbate tensions in an already volatile environment. The security situation remains precarious, with sporadic outbreaks of violence in the regions, while political tensions could flare up in the run-up to the December presidential and legislative elections. In this context, the authorities have adopted a comprehensive response plan aimed at containing the spread of the virus and at increasing state capacity to assist infected people.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet